2018
DOI: 10.1002/jgf2.160
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of methicillin‐resistant Staphylococcus aureus in community residents of Japan

Abstract: BackgroundTo implement effective precautions to avoid methicillin‐resistant Staphylococcus aureus (MRSA) nosocomial infections, it is important to clarify when, how, and from whom MRSA was transmitted to the patients. However, MRSA strains obtained from outpatient population were not analyzed, and the transmission routes of MRSA in the community are not completely understood. The purpose of this study was to clarify whether MRSA is spreading in community settings or whether MRSA transmission still occurs only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Methicillin‐resistant Staphylococcus aureus colonization was investigated in 45 healthcare professionals. The results were compared with previous MRSA surveillance data and are summarized in Table . The proportion of MRSA colonization was significantly higher among healthcare professionals (11.1%) than community residents (0.72%; P < 0.0001) or admission case (2.5%; P = 0.018).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Methicillin‐resistant Staphylococcus aureus colonization was investigated in 45 healthcare professionals. The results were compared with previous MRSA surveillance data and are summarized in Table . The proportion of MRSA colonization was significantly higher among healthcare professionals (11.1%) than community residents (0.72%; P < 0.0001) or admission case (2.5%; P = 0.018).…”
Section: Resultsmentioning
confidence: 98%
“…Multilocus sequence typing analysis revealed that five isolates from healthcare professionals consisted of two ST8 and three ST764 isolates. These results were combined with previous MRSA surveillance data and are summarized in Table . Both ST8 and ST764 strains were isolated from residents, admission cases, hospitalized patients, and healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] The prevalence of MRSA in the Japanese general population is estimated to be ≤ 5%. [46][47][48]; however, this prevalence might be higher among elderly adults owing to frailty, in comparison with younger people. [49] Furthermore, regional MRSA epidemics of community-acquired strains have recently occurred in Japan, which might affect MRSA prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the prevalence of communityassociated MRSA infection in Japan, Germany, Turkey, Taiwan, and Malta was found to be 0.94%, 1.2%, 1.2%, 1 3.8%, 1 and 8.81% 1 respectively. [8][9][10][11][12] This variation of nasal carriage rate of S. aureus in studies might be due to difference in the characteristics of the study population, quality of sampling, culturing techniques, geographical distribution, and diagnostic techniques. 13 A previous study reported an MRSA colonization rate in diabetics as 10.2%, whereas in another study it was 19% in diabetics on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%